ANALISIS ALOKASI DANA DESA (ADD) TERHADAP PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DESA PAYA ITIK KECAMATAN GALANG KABUPATEN DELI SERDANG - Ratna Dina Marviana; Novita Barus (UNIVERSITAS DHARMAWANGSA, 2022)
The Village Fund Allocation is a fund sourced from the Regency Regional Revenue and Expenditure Budget (APBD) which is allocated to the village government for the purpose of development and community empowerment. The purpose of this study is to find out how to manage the Village Fund Allocation in Paya Itik Village. This research was conducted due to the lack of transparency in the use of ADD so that the community did not participate in ADD funded activities. This research is expected to be useful for Paya Itik Village in an effort to improve the management of village fund allocations.The research method used is a qualitative approach with the research subject of Village Fund Allocation managers and the community. Data was collected by using observation, interview and documentation techniques. The techniques used in data analysis are data reduction, data presentation and conclusion drawing. The results showed that the planning and implementation of village fund allocation activities had been carried out as planned. Meanwhile, the Administration and Accountability of the Village Fund Allocation is still not optimal. Due to the transfer of duties by PTPKD and the delay in reporting accountability to the center. Meanwhile, accountability to the community has not been transparent because there are still many people who do not know the use of the Village Fund Allocation.